2008
DOI: 10.1007/s10633-007-9102-9
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal electroretinographical changes in monkeys with experimental ocular hypertension: a longitudinal study

Abstract: OHT does not always lead to ERG changes. Comparisons with fellow eyes using high contrast stimuli are more sensitive to detect changes related to OHT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Recently, Kremers et al [55] reported the results of a study of experimental glaucoma in cynomolgus monkeys in which numerous tests were performed during the period of elevated IOP. Unlike our study, they summed the absolute differences at each signal data point during the 0 to 90 ms interval of K1;no information was obtained regarding the individual wave features (e.g., N1 and P1) or the K2.1.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kremers et al [55] reported the results of a study of experimental glaucoma in cynomolgus monkeys in which numerous tests were performed during the period of elevated IOP. Unlike our study, they summed the absolute differences at each signal data point during the 0 to 90 ms interval of K1;no information was obtained regarding the individual wave features (e.g., N1 and P1) or the K2.1.…”
Section: Discussionmentioning
confidence: 99%
“…Multifocal electroretinography testing in nonhuman primates has been carried out with varied anesthetic regimens, e.g., ketamine and xylazine [1-4], ketamine with neuromuscular blocker intravenous infusion [5-6], ketamine or ketamine and xylazine and isoflurane with extraocular muscle blockade [7], and propofol with periodic injections of a neuromuscular blocker [8-10]. Some of the studies [5-6] [8-10] have incorporated the use of a systemic neuromuscular blocker.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the studies [5-6] [8-10] have incorporated the use of a systemic neuromuscular blocker. Our laboratory has used pentobarbital sodium and isoflurane anesthesia without a paralytic agent in previous investigations of the multifocal electroretinogram (mfERG) [11-14] in rhesus and cynomolgus macaques.…”
Section: Introductionmentioning
confidence: 99%